From superspreaders to disease hotspots: linking transmission across hosts and space. Issue 2 (19th December 2011) - Paull, Sara H; Song, Sejin; McClure, Katherine M; Sackett, Loren C; Kilpatrick, A Marm; Johnson, Pieter TJ
Abstract : Since the identification and imprisonment of "Typhoid Mary", a woman who infected at least 47 people with typhoid in the early 1900s, epidemiologists have recognized that "superspreading" hosts play a key role in disease epidemics. Such variability in transmission also exists among species within a community and among habitat patches across a landscape, underscoring the need for an integrative framework for studying transmission heterogeneity, or the differences among hosts or locations in their contribution to pathogen spread. Here, we synthesize literature on human, plant, and animal diseases to evaluate the relative influence of host, pathogen, and environmental factors in producing highly infectious individuals, species, and landscapes. We show that host and spatial heterogeneity are closely linked and that quantitatively assessing the contribution of infectious individuals, species, or environmental patches to overall transmission can aid management strategies. We conclude by posing hypotheses regarding how pathogen natural history influences transmission variability and highlight emerging frontiers in this area of study.